Програмний комплекс верифікації персональних даних веб-учасника - Федушко, Соломія; Сєров, Юрій (Видавництво Львівської політехніки, 2015)
This paper deals with сomputer-linguistic analysis of reliability of web-member socio-demographic characteristics. The architecture of program complex of webmember personal data verification is developed.
Keywords: верифікація; персональні дані; програмний комплекс; віртуальна спільнота; веб-учасник